2013
DOI: 10.1111/ene.12145
|View full text |Cite
|
Sign up to set email alerts
|

Blood alcohol concentration as a determinant of outcomes after traumatic spinal cord injury

Abstract: Our results, for the first time, show that the BAC at emergency admission does not adversely affect the patients' mortality, neurological impairment or functional disability over the course of the first year after SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
3
Order By: Relevance
“…24 Moreover, most of the traumatic events studied occurred on weekends, a period when alcohol consumption by the population exposed to this type of injury is intensified, and eleven of the thirteen victims of SCI who reported that they were under the effect of alcohol suffered MVAs. According to Furlan and Fehlings, 25 blood alcohol levels upon admission did not show any correlation with mortality, neurological or functional deficit over the first year after injury in humans; however, alcohol consumption is indicated as the main risk factor for the associated occurrence of cranial trauma in traumatic spinal cord injuries. 15 While in our sample, cranioencephalic trauma was the second most common type of associated lesion, Morais et al 21 reported it to be the most frequent variant.…”
Section: Resultsmentioning
confidence: 97%
“…24 Moreover, most of the traumatic events studied occurred on weekends, a period when alcohol consumption by the population exposed to this type of injury is intensified, and eleven of the thirteen victims of SCI who reported that they were under the effect of alcohol suffered MVAs. According to Furlan and Fehlings, 25 blood alcohol levels upon admission did not show any correlation with mortality, neurological or functional deficit over the first year after injury in humans; however, alcohol consumption is indicated as the main risk factor for the associated occurrence of cranial trauma in traumatic spinal cord injuries. 15 While in our sample, cranioencephalic trauma was the second most common type of associated lesion, Morais et al 21 reported it to be the most frequent variant.…”
Section: Resultsmentioning
confidence: 97%
“…Las personas con lesiones graves como una LM están en un nivel desproporcionadamente mayor de US y/o TUS que la población general (Kolakowsky-Hayner et al, 1999;Schandler, Cohen, y Vulpe, 1996;Schandler, Cohen, Vulpe y Frank, 1995;Smedema y Ebener, 2010;Wegener et al, 2012). Es más, como algunas investigaciones han señalado, el US también puede ser un factor importante que contribuye a sufrir una LM (Bombardier et al, 2004;Forchheimer et al, 2005;Garrison et al, 2004;Heinemann et al, 1988;Kolakowsky-Hayner et al, 1999;Krause et al, 2000;Krause, 2004;Levy et al, 2004;McKinley et al, 1999;Tate et al, 2004). Por tanto, este tema es de gran interés para profesionales sanitarios y científicos por su posible relación con la salud mental de los pacientes, la colaboración durante los procesos de rehabilitación y el funcionamiento posterior, así como en los estilos de vida elegidos después del alta (Bombardier y Rimmele, 1998;Frisbie y Tun, 1984;Njoki, Frantz y Mpofu, 2007;Post y van Leeuwen, 2012;Stroud et al, 2011).…”
Section: Discussionunclassified
“…En general, hay una amplia variedad de metodologías y variables medidas entre estudios. Gran parte de la literatura se centraba en la medición de ingesta de alcohol o de alcoholemias (Furlan y Fehlings, 2013;McKinley et al, 1999;Rothstein, Levy, Fecher, Gordon, y Bauman, 1992;Stroud et al, 2011;Turner et al, 2003). Varios estudios evaluaron tabaco y otras sustancias legales (p.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Trauma-related neurological dysfunction remains an important cause of long-term disability that encompasses cognitive and physical deficits, epilepsy and spinal cord injury sequelae that are not only of clinical but also of legal relevance [49,56,[204][205][206][207]. The role of rehabilitation and research into its best delivery and efficacy is an area that deserves greater attention.…”
Section: Recent Advances In Neurology 2013-2014mentioning
confidence: 99%